Pembiayaan Dalam Perspektif Ekonomi Dan Hukum - Muhammad Faris Al Hadi; Muhammad Fathir Alghifari; Priska Pebriana; Lulu Putia Zubir; Indah Permata Ali; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Financing is an essential instrument in the financial system that plays a significant role in supporting economic activities and promoting economic growth as well as public welfare. This study aims to analyze the concept and role of financing in economic activities, the legal basis and implementation mechanisms of financing in Indonesia, and the problems and settlement of financing from economic and legal perspectives. This research employs a normative legal research method with a juridical-normative approach, supported by library research on statutory regulations, academic literature, and data from financial authorities. The results indicate that financing contributes significantly to economic growth, particularly in the development of micro, small, and medium enterprises (MSMEs), and enhances the effective utilization of funds through the intermediation function of financial institutions. From a legal perspective, financing in Indonesia is regulated comprehensively under Law Number 10 of 1998 on Banking, the Indonesian Civil Code, and implementing regulations issued by Bank Indonesia and the Financial Services Authority. However, in practice, financing still faces challenges in the form of non-performing financing due to debtor default. Therefore, financing restructuring and the application of the prudential principle are essential measures to ensure legal certainty and maintain the stability of the financial system.